Measurement of telomere length in cells from pleural effusion: Asbestos exposure causes telomere shortening in pleural mesothelial cells. Issue 9 (10th August 2018) - Aida, Shinsuke; Aida, Junko; Naoi, Miho; Kato, Mai; Tsuura, Yukio; Natsume, Ichiro; Takubo, Kaiyo
Abstract : We estimated the telomere lengths of neoplastic and non‐neoplastic mesothelial cells and examined their correlation with asbestos exposure and the expression of markers of mesothelial malignancy. Cell blocks of pleural effusion obtained from 35 cases of non‐neoplastic disease (NN), 12 cases of malignant mesothelioma (MM) and 12 cases of carcinomatous effusion due to lung adenocarcinoma (LA) were examined. Fifteen of the 35 NN cases had pleural plaques (NNpp+) suggestive of asbestos exposure, and the other 20 cases had no pleural plaques (NNpp‐). Telomere length was measured using the tissue quantitative fluorescence in situ hybridization method, and expressed as normalized telomere‐to‐centromere ratio. NN cases had significantly longer telomeres than MM ( P < 0.001) and LA ( P < 0.001) cases. Telomeres in NNpp+ cases were slightly shorter than those of NNpp‐ cases ( P = 0.047). MM and LA showed almost the same telomere length. NN cases with shorter telomeres tended to show aberrant expression of epithelial membrane antigen (EMA), CD146, glucose transporter 1 (GLUT1) and IGF‐II messenger RNA‐binding protein 3 (IMP3). These results suggest that telomere shortening and subsequent genetic instability play an important role in the development of MM. Measurement of telomere length of cells in pleural effusion might be helpful for earlier detection of MM.